¿Extinción de la interdicción y la curatela? Comentarios a una audaz y polémica decisión judicial - Cieza Mora, Jairo Napoleón (2015)
In this paper, the author will analize the sentence issued by Judge Edwin Romel Bejar Rojas from the Third Judge of the Third Family Court in Cuzco. The sentence was issued in a process that had began with a lawsuit followed by a mother against her children in order to declared them without capacity to act (two of the sons have mental disabilities). In this procedure, the Judge didn’t use the rules relating to civil capacity of natural persons. In this paper, the extinguish of the curatela is also analyzed. These issues are being discussed in other legal systems and this paper will discuss them, as well.